Analisis Kepribadian Tokoh Alara Dalam Novel Lara Rasa Karya Nureesh Vhalega Berdasarkan Teori Kebutuhan Hierarki Maslow - Debby Irola; Reni Sofia Ningsih; Eva Dwi Kurniawan (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The purpose of this research is to analyze the personality of Alara. The material objects used in the novel entitled